Peningkatan Kepatuhan Minum Obat Pasien Lupus Eritematosus Sistemik - Heppy Roosarina Rahayu Dewi; DetyMulyanti (Universitas Katolik Widya Karya Malang, 2023)
Systemic Lupus Erythematosus (SLE) is an important systemic autoimmune disease. Women are ten times more at risk of developing LES than men. The etiology of SLE is not fully understood and the pathophysiology involves genetic, immunological, endocrine and environmental factors. SLE is a chronic disease with periods of remission and relapse, so it requires different management and a long time. Medication adherence is required so that treatment goals can be achieved. Medication adherence rates in people with lupus have been reported from various studies to be 31.7-45.9%. Non-adherence to treatment for SLE causes an increase in visits to the emergency department and also hospitalization. There are two kinds of factors that influence medication adherence, intentional non-adherence and non-intentional non-adherence. Efforts are needed to improve and increase medication adherence by considering these both factors.